Neomillspaughia hondurensis (Polygonaceae), a new species from Central America - Ortiz-Díaz, Juan Javier; Arnelas, Itziar; Tun, Juan; Flores, José Salvador (Phytotaxa, 2013)
A new species Neomillspaughia hondurensis (Polygonaceae) from Honduras is described and illustrated. This species is morphologically and ecollogicaly different from the other two currently known Neomillspaughia species, being more related to N. emarginata than to N. paniculata. A comprehensive comparison and a key for the three species are provided. Se describe e ilustra la nueva especie Neomillspaughia hondurensis (Polygonaceae) de Honduras. Esta especie es morfológicamente y ecológicamente diferente de las dos únicas especies de Neomillspaughia, estando más relacionada con N. emarginata que con N. paniculata. Se proporciona información comparativa de la nueva especie con las especies relacionadas y una clave para la identificación de las mismas.